PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. KMK GLOBAL SPORTS - farhan, akhmad; Abdillah, Juandi; Windasari, Depina (JUBISMA, 2025)
This study aims to analyze the effect of compensation and job satisfaction on employee productivity at PT. KMK Global Sports. Based on the results of the analysis, compensation has a positive and significant effect on employee productivity. In addition, job satisfaction is also proven to have a significant effect on work productivity. This study uses a quantitative approach with three variables studied, namely compensation and job satisfaction as independent variables, and employee productivity as the dependent variable. The primary data used in this study were obtained by distributing questionnaires to employees working in the production division. To analyze the collected data, a series of tests can be carried out, such as validity tests, reliability tests, classical assumption tests, and statistical analysis in the form of correlation, coefficient of determination, regression, and hypothesis tests. The results of the analysis show that compensation has a positive and significant effect on employee productivity partially, which means that the better the compensation received by employees, the higher their productivity. In addition, the results of the study also show that compensation and job satisfaction simultaneously have a positive and significant effect on employee productivity in the production department of PT. KMK Global Sports. This study provides implications that companies need to pay attention to both factors, as both have been shown to play an important role in improving employee performance and overall productivity. Based on these findings, it is recommended that companies continue to improve compensation and job satisfaction policies to support productivity optimization in the future.